Revisiting the Role of Radiation Therapy in Chondrosarcoma: A National Cancer Database Study. (13th October 2019) - Catanzano, Anthony A.; Kerr, David L.; Lazarides, Alexander L.; Dial, Brian L.; Lane, Whitney O.; Blazer, Dan G.; Larrier, Nicole A.; Kirsch, David G.; Brigman, Brian E.; Eward, William C.
Abstract : Background . Although chondrosarcomas (CS) are mostly considered radioresistant, advancements in radiotherapy have brought attention to its use in these patients. Using the largest registry of primary bone tumors, the National Cancer Database (NCDB), we sought to better characterize the current use of radiotherapy in CS patients and identify any potential survival benefit with higher radiation doses and advanced radiation therapies. Methods . We retrospectively analyzed CS patients in the NCDB from 2004 to 2015 who underwent radiotherapy. The Kaplan–Meier method with statistical comparisons was used to identify which individual variables related to dosage and delivery modality were associated with improved 5-year survival rates. Multivariate proportional hazards analyses were performed to determine independent predictors of survival. Results . Of 5, 427 patients with a histologic diagnosis of chondrosarcoma, 680 received a form of radiation therapy (13%). The multivariate proportional hazards analysis controlling for various patient, tumor, and treatment variables, including RT dose and modality, demonstrated that while overall radiation therapy (RT) was not associated with improved survival (HR 0.96, 95% CI 0.76–1.20), when examining just the patient cohort with positive surgical margins, RT trended towards improved survival (HR 0.81, 95% CI 0.58–1.13). When comparing advanced and conventional RT modalities, advanced RT was associated with significantly decreased mortality (HR 0.55, 95% CI 0.38–0.80). However, advanced modality and high-dose RT both trended only toward improved survival compared to patients who did not receive any RT (HR 0.74, 95% CI 0.52–1.06 and HR 0.93, 95% CI 0.71–1.21, respectively). Conclusions . Despite the suggested radioresistance of CS, modern radiotherapies may present a treatment option for certain patients. Our results support a role for high-dose, advanced radiation therapies in selected high-risk CS patients with tumors in surgically challenging locations or unplanned positive margins. While there is an associated survival rate benefit, further, prospective studies are needed for validation.